Catalysts for Sustainable Hydrogen Production: Preparation, Applications and Process Integration - Martino, Marco; Ruocco, Concetta (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this book, we propose a collection of scientific and review articles on the production of hydrogen. The articles focus on the controlled storage and release of hydrogen; on the production of hydrogen from reforming from renewable sources, water splitting, and biological and photonic methods; on the intensification of the water gas shift process; and on the integration with purification methods such as pressure swing adsorption.